Peran Motivasi Dan Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan Di PT. PLN Kota Solok - Sriyanti, Esi; Mursalini, Wahyu Indah; Maishara, Yuni (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Even a state-owned enterprise like PT. PLN must optimize all electricity-related services. All PT. PLN staff are required to perform this important obligation. Consequently, PT. PLN requires personnel who exhibit exemplary performance. This study seeks to examine the impact of employee performance on motivation and work discipline. The research concentrated on the personnel of PT. PLN Kota Solok. The study's population consisted of all employees of PT. PLN Kota Solok, with 57 persons undergoing quantitative analysis. Consequently, the sampling method employed will be the whole sample technique, as the overall population comprises fewer than 100 individuals. The findings of the multiple linear regression analysis indicate that work motivation and work discipline positively influence employee performance at PT. PLN Kota Solok. The coefficient of determination of 0.662 signifies that work motivation and discipline account for 66.2% of the variance in employee performance at PT. PLN Kota Solok. The t-test results indicate that work motivation influences employee performance. Conversely, Work Discipline exerts a significant impact on Employee Performance. The F test results indicate that employee performance at PT. PLN Kota Solok is concurrently influenced by work motivation and work discipline.